The new bohemians handbook ebook Come home to good vibes. - Blakeney, Justina (2022)
"Justina's style is so warm and colorful . . . All her plants and pallets and prints are put together in ways that are beyond stylish. It is art." —Drew Barrymore The New Bohemian Handbook  guides readers in beautifully simple techniques for adding good vibes and style to living spaces. Packed with hundreds of ideas for bringing positive energy to your home, the book features exercises and activities for thinking about rooms in new ways.   With Justina Blakeney's expert guidance, learn how to rearrange, paint, prop, and plant your way to a home that's fresh and inspiring. Uncover your "spirit environment" and learn how to use color and scent to enhance mood, productivity, and relaxation. Revel in Justina's encouraging advice ("you got this!"), and easily and affordably turn any dwelling into a personal sanctuary. "An indispensable manual to living in a home that's pretty, restful, groovy and 100% you. This is my spirit book! Finally a book that offers specific, helpful ways to make a home feel original, beautiful and, most importantly, like a haven for its homeowner." —Sophie Donelson, Editor in Chief, House Beautiful "With Ms. Blakeney as guide, princes, plumbers and poets alike can readily replicate the charm and ease of these featured interiors—from tiny urban studios to suburban domiciles to rustic retreats." — The Wall Street Journal "As vibrant, rule-breaking and out the box as she showed in her first book . . . It's part book, part yoga lesson as Blakeney walks readers through finding clarity, flow, growth and harmony in our homes." — The Detroit News "Full of ideas for bringing positive energy to your home." — The Washington Post